2009
DOI: 10.1152/ajpregu.90697.2008
|View full text |Cite
|
Sign up to set email alerts
|

Toward an animal model of childhood-onset obesity: follow-up of OLETF rats during pregnancy and lactation

Abstract: A. Toward an animal model of childhood-onset obesity: follow-up of OLETF rats during pregnancy and lactation. Am J Physiol Regul Integr Comp Physiol 296: R224 -R232, 2009. First published November 26, 2008 doi:10.1152/ajpregu.90697.2008.-The Otsuka LongEvans Tokushima Fatty (OLETF) rat model of obesity (a spontaneous CCK1 receptor knockout) has been extensively studied as model of hyperphagia-induced obesity. In previous studies, young OLETF rats presented abnormal eating patterns [compared with Long-Evans To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…We have previously demonstrated that OLETF males and females are born heavier and present more white fat soon after birth (46). The developmental follow-up conducted here has exposed an abrupt change during and after the period of sexual maturation (PND 90 in the males and PND 120 in the females), especially in the males, where body weight, fats, and adipocyte area sharply increased.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We have previously demonstrated that OLETF males and females are born heavier and present more white fat soon after birth (46). The developmental follow-up conducted here has exposed an abrupt change during and after the period of sexual maturation (PND 90 in the males and PND 120 in the females), especially in the males, where body weight, fats, and adipocyte area sharply increased.…”
Section: Discussionmentioning
confidence: 54%
“…We have recently reported that females present a significantly higher level of adipocyte cell increase in the preweaning period, compared with the males (46). Here, the first weeks postweaning appeared to be a continuation of this pattern, with females presenting more fat cells than males until PND 48; from then on, the cell number in the females remained constant.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…OLETF rats exhibit hyperphagia and eventually become obese, an effect primarily due to the lack of CCK-1 receptors on their genotypic background. OLETF rats show pre-obese characteristics from infancy and sex-differences in patterns of obesity emergence (Schroeder et al, 2009a; Schroeder et al, 2009b). Research has showed that adult OLETF rats demonstrate high avidity for sucrose (De Jonghe et al, 2005; Hajnal et al, 2005), greater dopamine (DA) response to cocaine and amphetamine in the Nucleus accumbens (Nac) region (Feifel et al, 2003) and low D2R function and binding in the Nac shell area (Hajnal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%